HL-IR mediates cinnamaldehyde repellency behavior in parthenogenetic Haemaphysalis longicornis. - Ceyan Kuang; Han Shi; Jie Cao; Yongzhi Zhou; Houshuang Zhang; Yanan Wang; Jinlin Zhou (PLoS Neglected Tropical Diseases)
Chemical repellents against arthropods have limitations in terms of toxicity and resistance. Natural plant compounds can be utilized as alternatives for developing environmentally friendly repellents for humans and animals. A variety of plant essential oils exhibit strong repellent effects against ticks; however, the mechanisms of action against ticks remain unknown. Here, we investigated the repellency of cinnamaldehyde, a primary compound found in cinnamon oil, and demonstrated that it affected the electrophysiological responses on Haller's organs of parthenogenetic Haemaphysalis longicornis. Transcriptome data indicated that the cinnamaldehyde response was linked to ionotropic receptor (HL-IR) at various tick developmental stages. HL-IR was widely expressed in a variety of tissues and developmental stages of ticks according to RT-qPCR. In situ hybridization results showed that HL-IR was highly expressed on Haller's organs of the ticks. Microinjection of HL-IR double-stranded RNA (dsRNA) showed that reduced transcript levels led to significant decreases in the tick repellency rate from cinnamaldehyde and the EAG response of Haller's organ. Experiments using competitive fluorescence binding and mutation sites showed that 218ASN was the critical binding site for cinnamaldehyde and HL-IR. We conclude that Haller's organ of ticks expresses HL-IR, and that this interaction mediates tick-repellent behavior by binding to cinnamaldehyde.